Key Considerations in Delivering Trauma-Informed Professional Learning for Educators - Koslouski, Jessica B.; Chafouleas, Sandra M. (Frontiers in Education, 2022)
More than half of U.S. adults have experienced potentially traumatic events. Given that reminders of these events can spur re-traumatization, facilitators of professional learning about trauma-informed practices must be intentional in their delivery to avoid re-traumatizing participants. Based on our experience delivering professional learning in trauma-informed practices to K-12 educators broadly, we outline key strategies for facilitators. We organize these strategies using the United States Substance Abuse and Mental Health Services Administration’s (SAMHSA) 6 key principles of a trauma-informed approach: safety; trustworthiness and transparency; peer support; collaboration and mutuality; empowerment, voice, and choice; and cultural, historical, and gender issues. Within each principle, we offer three strategies along with a rationale and supporting research for each. Example strategies include learning about the school, staff, and students as much as possible before leading the training (collaboration and mutuality), conveying that there is not a “one size fits all” answer to addressing student trauma (trustworthiness and transparency), and providing time for educators to reflect on how to apply the content to their classrooms (empowerment, voice, and choice). We demonstrate alignment of these strategies with implementation supports of trauma-informed learning (e.g., relevance to school community) and provide facilitators with action planning questions to guide selection of recommended strategies. Finally, we conclude with important next steps for research on the delivery of trauma-informed professional learning.